On the determination of gravity wave momentum flux from GPS radio occultation data - A. Faber; P. Llamedo; T. Schmidt; A. de la Torre; J. Wickert (Atmospheric Measurement Techniques, 2013)
Global Positioning System (GPS) radio occultation (RO) is a well-established technique for obtaining global gravity wave (GW) information. RO uses GPS signals received by low Earth-orbiting satellites for atmospheric limb sounding. Temperature profiles are derived with high vertical resolution and provide a global coverage under any weather conditions, offering the possibility of global monitoring of the vertical temperature structure and atmospheric wave parameters. The six-satellite constellation COSMIC/FORMOSAT-3 delivers approximately 2000 temperature profiles daily. In this study, we use a method to obtain global distributions of horizontal gravity wave wavelengths, to be applied in the determination of the vertical flux of horizontal momentum transported by gravity waves. Here, a method for the determination of the real horizontal wavelength from three vertical profiles is applied to the COSMIC data. The horizontal and vertical wavelength, the specific potential energy (Ep), and the vertical flux of horizontal momentum (MF) are calculated and their global distribution is discussed.